2006
DOI: 10.1191/0265659006ct311xx
|View full text |Cite
|
Sign up to set email alerts
|

Performance of typically-developing school-age children with English as an additional language on the British Picture Vocabulary Scales II

Abstract: This study provides preliminary indications of the performance of typically developing children with English as an additional language (EAL) on the British Picture Vocabulary Scales II [BPVS II]. One-hundred and sixty-five children aged four to nine years took part in the study, 69 monolingual English speakers and 96 with EAL. The results indicate an effect of both age and language status, with the EAL children scoring proportionally lower at younger ages. There was a narrowing gap between the scores of EAL an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
35
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 22 publications
(20 reference statements)
7
35
1
1
Order By: Relevance
“…However, the evidence for differences in vocabulary development in bilingual and monolingual children is mixed, depending on the ages of the children and whether receptive or productive vocabulary is assessed. A smaller receptive vocabulary in each language compared with monolinguals has been reported in samples of preschool- and school-aged children (Bialystok, Barac, Blaye, & Poulin-Dubois, in press; Bialystok, Luk, Peets, & Yang, 2010; Mahon & Crutchley, 2006), but other studies have shown that the receptive vocabulary of school-aged children is close to that of monolinguals (Cromdal, 1999; Yan & Nicoladis, 2009). With respect to measuring expressive language, school-aged bilinguals tend to have a smaller vocabulary even when both languages are combined (Yan & Nicoladis, 2009).…”
Section: Introductionmentioning
confidence: 82%
“…However, the evidence for differences in vocabulary development in bilingual and monolingual children is mixed, depending on the ages of the children and whether receptive or productive vocabulary is assessed. A smaller receptive vocabulary in each language compared with monolinguals has been reported in samples of preschool- and school-aged children (Bialystok, Barac, Blaye, & Poulin-Dubois, in press; Bialystok, Luk, Peets, & Yang, 2010; Mahon & Crutchley, 2006), but other studies have shown that the receptive vocabulary of school-aged children is close to that of monolinguals (Cromdal, 1999; Yan & Nicoladis, 2009). With respect to measuring expressive language, school-aged bilinguals tend to have a smaller vocabulary even when both languages are combined (Yan & Nicoladis, 2009).…”
Section: Introductionmentioning
confidence: 82%
“…For instance, in a study conducted by Carlo et al (2004), monolingual U.S. students scored higher than their bilingual peers on the Peabody Picture Vocabulary Test Revised (PPVT-R). Limbird (2007) found less well-developed vocabulary knowledge among German-Turkish bilingual students in comparison to monolingual German students (see also Kieffer & Lesaux, 2012;Mahon & Crutchley, 2006). Moreover, Verhoeven and Vermeer (2006) reported increasing group differences in vocabulary knowledge from grade 3 to grade 6.…”
Section: Reading Literacy Of Students With Immigrant Backgroundsmentioning
confidence: 99%
“…A further issue that may influence the validity of these results stems from the fact that there was no control group for the measurements taken after 6 months of frequency compression use. It is possible, therefore, that the differences in scores may be due to maturational effects (see for example, Mahon and Crutchley, 2006, for details of age related changes in receptive vocabulary) or to acclimatisation to other features of the hearing aids, rather than to frequency compression specifically. In particular, maturational effects may have influenced scores on the BKB-SIN as the stimuli used contain Ellis & Munro, Frequency compression hearing aids 8 large amounts of contextual information, which a child may be better able to use as they develop and their receptive vocabulary improves.…”
Section: Auditory Acclimatisationmentioning
confidence: 99%